PERAN TEKNOLOGI SEBAGAI KATALISATOR DALAM IMPLEMENTASI KETERAMPILAN MENGAJAR ABAD 21 DI SD N 15 SRAGEN - Rana Dinar Algadisa Rana Dinar Algadisa, Melodia Fairus Rahma, Fikriana Khusnaini, Kalid Ardhi Susan (Elementary School and Education Journal, 2026)
Abstract: In the era of globalization in the 21st century, mastering relevant and adaptive competencies is key to increasing human resource competitiveness. Therefore, utilizing teaching materials integrated with technology is crucial to facilitate effective and efficient learning processes. However, the lack of innovation and creativity in integrating technology into teaching materials can hinder the achievement of learning objectives and expected competencies, so efforts need to be made to improve the quality and relevance of teaching materials used. This study examines the process of technology-based science learning in elementary schools using the Problem-Based Learning (PBL) model, which poses a challenge for teachers in implementing technology-based learning processes. This study aims to identify the needs for opportunities to develop teaching materials integrated with technology, with the hope of increasing students' opportunities to improve their abilities, both literacy and active practice. This study was conducted qualitatively using interview and needs analysis data collection techniques. The results of this study show that teachers use various teaching materials provided by the school to support learning. The results of this study also show that teachers have a positive opinion about the development of technology in learning. Through this research, it is expected to become new knowledge and consideration for teachers in developing and implementing technology-based teaching materials to support student learning processes.